DERMATOLOGIC GELS SPREADABILITY MEASURING METHODS COMPARATIVE STUDY - ELENA O., BAKHRUSHINA; MARIA N., ANUROVA; MICHAEL S., ZAVALNIY; NATALIA B. , DEMINA; ALEXANDER I., BARDAKOV; IVAN I., KRASNYUK (International Journal of Applied Pharmaceutics, 2022)
Objective: The main objective of our study is the comprehensive analysis and characterization of the existing spreadability evaluation strategies, the comparison of the obtained results reproducibility and convergence through the example of the 9 most widely used dermatological gels. Methods: Dolobene®, Flucinar®, Ketorol®, Contractubex®, Dr. Theiss Venen gel®, Solcoseryl®, Deep Relief®, Hepatrombin® pharmacopoeia gel samples were analyzed using parallel-plate, “slip and drag”, and viscometry methods. Analysis was performed in flow mode at 32±0.2 °C, over shear rates ranging from 0 to 350 s−1, increasing over a period of 120 s, and was maintained at the superior limit for 10 s and then decreased during the same period. At least 5 replicates of each sample were evaluated, and the upward flow curves were fitted using the Casson mathematical model. Results: Solcoseryl® and Dolobene® showed the best spreadability in the parallel-plate method (3115.66±50.00 and 3316.63±50.00, respectively); Contractubex® and Dolobene showed the best spreadability in the “slip and drag” test (73.46±0.5 and 18.32±0.5, respectively); Solcoseryl® and Contractubex® showed the best spreadability in the viscometry test (43.86±0.5 and 76.92±0.5, respectively). Conclusion: This study analyzed the existing methods for determining the spreadability using commercially available samples of the dermatological gels as examples. The viscometric and the "Slip and drag" methods use different characteristics of spreadability, giving a complex evaluation of the measured parameter in vitro. Therefore, the combination of these two methods has the greatest prospects for reliable determination of this indicator.